Design, Synthesis and Antibacterial Studies of Novel Cationic Amphipathic Cyclic Undecapeptides and Their Linear Counterparts against Virulent Bacterial Strains - Hisham N. Farrag; Toshinari Maeda; Tamaki Kato (MDPI AG, 2021)
Bacteria have acquired resistance against almost all antibiotics because of the misuse of antibacterial agents and long periods of treatment. Antimicrobial peptides (AMPs) are one of the most encouraging candidates to solve this problem, as they possess high prokaryotic selectivity, and affect the bacteria by a unique mode of action. Novel cyclic undecapeptides (QNRNFYFNRNQ and QNRNFHFNRNQ) and their linear counterparts were investigated for their antibacterial activity against virulent strains. The minimal inhibitory concentration (MIC) values showed that tyrosine and histidine AMPs have promising antibacterial activity against virulent bacteria. The MIC values against the P. aeruginosa PA14, E. coli O157:H7 CR3, S. aureus 209P, and B. subtilis ATCC 6633 bacterial strains were evaluated for the cyclic peptide containing tyrosine, and their values were 6.25, 12.5, 12.5, and 12.5 µM, respectively. Meanwhile, for the linear form, they were 9.3, 12.5, 12.5, and 12.5 µM, respectively. The cyclic-peptide-containing histidines' MIC values were 6.25, 3.1, 6.25, and 3.1 µM, respectively. Meanwhile, for the linear form, they were 3.1, 3.1, 3.1, and 6.25 µM, respectively. The antibacterial activities of the new AMPs were compared with that of gentamicin sulfate, and showed relatively higher potencies. Time-inhibition studies demonstrated the rapid antibacterial effects of the novel AMPs, which were more likely to be concentration-dependent, rather than time-dependent. At double the MIC concentration, all of the tested peptides exhibited relatively stable antibacterial effects up to 24 h, especially the peptides containing tyrosine, which showed an improved antibacterial effect.